Energy band alignment at the heterointerface between CdS and Ag-alloyed CZTS - Gansukh, Mungunshagai (Sci Rep, 2020)
Energy band alignment at the heterointerface between CdS and kesterite Cu(2)ZnSnS(4) (CZTS) and its alloys plays a crucial role in determining the efficiency of the solar cells. Whereas Ag alloying of CZTS has been shown to reduce anti-site defects in the bulk and thus rise the efficiency, the electronic properties at the interface with the CdS buffer layer have not been extensively investigated. In this work, we present a detailed study on the band alignment between n-CdS and p-CZTS upon Ag alloying by depth-profiling ultraviolet photoelectron spectroscopy (UPS) and X-ray photoelectron spectroscopy (XPS). Our findings indicate that core-level peaks and the valence band edge of CdS exhibit a significant shift to a lower energy (larger than 0.4 eV) upon the etching of the CdS layer, which can be assigned due to band bending and chemical shift induced by a change in the chemical composition across the interface. Using a simplified model based on charge depletion layer conservation, a significantly larger total charge region depletion width was determined in Ag-alloyed CZTS as compared to its undoped counterpart. Our findings reveal a cliff-like band alignment at both CdS/CZTS and CdS/Ag-CZTS heterointerfaces. However, the conduction-band offset decreases by more than 0.1 eV upon Ag alloying of CZTS. The approach demonstrated here enables nanometer-scale depth profiling of the electronic structure of the p–n junction and can be universally applied to study entirely new platforms of oxide/chalcogenide heterostructures for next-generation optoelectronic devices.